Defensive role of silibinin against arsenic induced oxidative stress mediated dyslipidemia and neurotoxicity in rats - Muthu, Muthumani; Naroem Chanu, Sumedha; Kalist, Shagirtha; Prabu, Milton (International Journal of Pharmacology and Toxicology, 2016)
Arsenic (As) is an environmental toxic metalloid that is present in everywhere such as air, water and soil. Generally, inorganic arsenic has a tendency to be more toxic than organic arsenic. The present study was designed to determine whether oral administration of silibinin (SB), which has been shown to have substantial antioxidant properties, when pre-administered (75 mg/kg body weight) once daily for 4 weeks along with arsenic (5 mg/kg) would prevent arsenic-induced changes in antioxidant defense system, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX),glutathione-S-transferase (GST),glutathione reductase (GR), glucose-6-phosphate dehydrogenase (G6PD), reduced glutathione (GSH), total sulfhydryl groups (TSH) and vitamin C in rat brain regions such as cortex, striatum, cerebellum, hippocampus and brain stem. Our study also examined the effect of SB over arsenic-induced reactive oxygen species (ROS) production and lipid peroxidation level (LPO) and protein carbonyl content (PC) in distinct brain regions of rats. Moreover, As also alters the lipid profiles such as total lipids, phospholipids, cholesterol, cerebrosides and gangliosides in various regions of the brain. Pre-administration of SB restores the altered enzymatic and non-enzymatic antioxidants, lipid profiles and also markedly reduced the ROS, LPO, PC and accumulation of As in various regions of the brain. These results suggested that arsenic-induced deficits in antioxidant enzyme activities and increase in ROS production and lipid peroxidation levels in brain regions can be remarkably prevented by pre-administration of SB.Â